(untitled) (SCIÉNDO INGENIUM, 2024)
In the realm of Newtonian fluids, fundamental conservation laws such as those governing mass, momentum, and energy are rigorously upheld within absolute reference frames. However, within the framework of special relativity and the concept of space -time, the notions of separate conservation of mass and momentum no longer hold. Instead, the theory relies on Lorentz transformations and relative reference systems, typically denoted as S and S’, moving uniformly relative to each other, each with its own temporal framework. Within the context of special relativity, particularly in the study of particles, significant findings pertain to the energy-momentum vector. These findings underscore the necessity, when studying fluids within inertial frames, to apply conservation principles to the energy-momentum tensor.